Short-selling bans and bank stability - Alessandro Beber; Daniela Fabbri; Marco Pagano; Saverio Simonelli (European Systemic Risk Board (ESRB), European System of Financial Supervision, 2018)
In both the subprime crisis and the euro-area crisis, regulators imposed bans on short sales, aimed mainly at preventing stock price turbulence from destabilizing financial institutions. Contrary to the regulators' intentions, financial institutions whose stocks were banned experienced greater increases in the probability of default and volatility than unbanned ones, and these increases were larger for more vulnerable financial institutions. To take into account the endogeneity of short sales bans, we match banned financial institutions with unbanned ones of similar size and riskiness, and instrument the 2011 ban decisions with regulators' propensity to impose a ban in the 2008 crisis.
Keywords: G01; G12; G14; G18; 330; short-selling; ban; financial crisis; bank stability; systemic risk